Consumer Preferences in Traditional Snacks, Bipang (Case Study of Pak Tani’s Bipang Company in Pasuruan) - Susanti, Tania; Utami, Christina Whidya (Review of Management and Entrepreneurship, 2023)
There is a shift in people's attitudes and interest in traditional snacks due to the influence of globalization and the perception that traditional snacks are out of date, causing the abandonment of these traditional snacks. The Covid-19 pandemic has added to the decline in income in many business sectors. This impact was also experienced by the Pak Tani’s bipang company, which has existed since 1976. For this reason, it is necessary to do a way to attract public interest in bipang products by innovating the flavor, product size, packaging design and accessibility. This study aimed to determine consumer preferences for traditional bipang snacks. The research conducted in October – November 2022 with a total sample were 400 respondents from Surabaya residents, which was carried out using a purposive sampling technique by distributing questionnaires. Respondents were asked to determine the combination of attributes from the most preferred to least preferred. This study uses descriptive quantitative methods using conjoint analysis techniques. The results showed that respondents liked bipang products with cheese flavor, bite size, standing pouch packaging design with zipper and offline accessibility. Based on the importance value factor, the order of the most important variables for respondents is flavor. Keywords: conjoint analysis, consumer preferences